PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA WISATA MENARI DUSUN TANON DESA NGRAWAN KECAMATAN GETASAN KABUPATEN SEMARANG - Octaviana, Rica; Warsono, Hardi (Journal of Public Policy and Management Review, 2020)
Abstract The existence of community empowerment in the Menari Tourism Village was an initiation by the local community and there is no support from the government and even Pokdarwis was an independent formation of the community. This is not suitable with Law Number 23 of 2014 concerning Regional Government article 12 paragraph 2 which states that one of the mandatory non-basic government affairs is the implementation of community empowerment. This study aims to analyze the efforts of community empowerment conducted by Menari Village’s Pokdarwis and the factors that influence it. The method used is a qualitative method with data collection techniques, namely interviews and literature study, data validity using triangulation techniques. The results showed that the effort to empower the community was not only carried out by Pokdarwis but there were also other parties involved. The parties involved included: Ngrawan Village Government, Tourism Office, Astra Company, and Sultan Agung University. Community empowerment efforts undertaken by these parties include the development of human resources; the development of the Dancing Village through marketing and partnership relations; and management of the physical environment. Supporting factors: a massive initiator's invitation, people's enthusiasm for change, the concept of local wisdom, and a willingness to explore. Inhibiting factors: quality of human resources, lack of government support, and jealousy of other hamlets. The recommendation that can be given in this study is that the government can legalize the Menari Village’s Pokdarwis so that its tasks and functions can be maximized properly